STRATIGRAFIA SEQUENZIALE DELLA SUCCESSIONE OLIGO-MIOCENICA DELLE LANGHE, BACINO TERZIARIO LIGURE-PIEMONTESE (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1992)
The Piedmont Tertiary Basin (PTB) is bounded southwards and westwards by the Western Alps, and northwards by the north-western end of the Apennines. It develops internally to a south-dipping suture zone, on a basement consisting of allochthonous alpine and apenninic units. The PTB history began at the end of the Eocene and has continued through the Oligocene, under mainly extensional tectonics conditions, and the Miocene, in a regime dominated by prevailing compressive phases. The PTB is filled by a more than 4,000 m thick succession of siliciclastic sediments. In the Langhe region, three groups of depositional sequences were recognized, bottom to top. Group A consists of continental to coastal conglomerates, shallow water sandstones and hemipelagic mudstones with thickness ranging from a few tens of metres to more than 600 m. Two depositional sequences (Early Oligocene; locally Late Eocene?) characterize this group. Group B is represented by six depositional sequences (B1 to B6; Late Oligocene-Burdigalian), each consisting of turbiditic sandstones and subordinate resedimented conglomerates in the lower part, and of hemipelagic mudstones with intercalated thin-bedded turbidites in the upper part. Total thickness of group B may be over 1,000 m. Group C shows six depositional sequences (C1 to C6; Late Burdigalian-Early Tortonian), consisting of turbidite systems, with sandstone/mudstone ratio from >>1 to 1, at the depocentres, and of mudstones on the slopes bounding the basin. Total thickness may be over 2,000 m. Synsedimentary tectonic activity is indicated by the following: a) angular unconformities, at the passage B1-B2 and at the lower boundary of sequence B5/B6; b) onlap of turbiditic sandstones on slightly folded mudstones (B1-B2 and B2-B3 sequence boundaries); c) vertical and lateral evolution of the facies which differs from that ofthe models proposed for eustatically controlled sequences (C1, C2 and C5). On the basis of biostratigraphic data, C1-C2 and C2-C3 boundaries correlate respectively with the 16.5 and 15.5 MA sequence boundaries of Haq et al. (1988). It is possible that the boundary between group A sequences and sequence B1 corresponds to their 30.0 MA boundary. B4-B5 sequence boundary, characterized by t long hiatus, probably correlates with the events dated 22.0/21.0 MA. By taking into account: a) the forementioned correlations; b) the stratigraphic setting and number of sequence boundaries between the 3O.O MA, 22.0/21.0 MA and 16.5 MA boundaries; c) the stratigraphic setting of the three sequence boundaries above the 15.5 MA boundary (all of Serravallian age), it is possibleto correlate the observed depositional sequences with the third order global cycles of Haq et al. (1988). Therefore, the global eustatic signal has not been obliterated in the studied area, in spite of the intense synsedimentary tectonic activity.
Keywords: Sequence stratigraphy; Tertiary Piedmont Basin; Italy.